Optical Fiber Pressure Sensor with Self-Temperature Compensation Structure Based on MEMS for High Temperature and High Pressure Environment - Ke Li; Yongjie Wang; Gaochao Li; Zhen Xu; Yuanyuan Liu; Ancun Shi; Xiaoyan Yu; Fang Li (Photonics)
To meet the pressure measurement requirements of deep earth exploration, we propose an OFPS (optical fiber pressure sensor) with self-temperature compensation based on MEMS technology. A spectral extraction and filtering algorithm, based on FFT (fast Fourier transform), was designed to independently demodulate the composite spectra of multiple FP (Fabry–Pérot) cavities, enabling the simultaneous measurement of pressure and temperature parameters. The sensor was fabricated by etching on an SOI (silicon on insulator) and bonding with glass to form pressure-sensitive FP cavities, with the glass itself serving as the temperature-sensitive component as well as providing temperature compensation for pressure sensing. Experimental results showed that within the pressure range of 0–100 MPa, the sensor exhibited a sensitivity of 0.566 nm/MPa, with a full-scale error of 0.34%, and a linear fitting coefficient (R2) greater than 0.9999. Within the temperature range of 0–160 °C, the temperature sensitivity of the glass cavity is 0.0139 nm/°C and R2 greater than 0.999.